ENERGY TRANSITION: Hydrogen production plant in Helguvík, Iceland. An architectural approach to green industry - Davíð Snær Sveinsson 1990- (2022)
This text is a short analysis of the social, political and technological setting of a hydrogen plant in Helguvík for the purpose of an architectural design. The energy transition in Iceland is of global significance. Supplementing fossil-fuels for sustainable energy where direct electricity does not apply, calls for major changes in energy infrastructure. Iceland is a perfect place to explore hydrogen production and utilization due to its abundant renewable energy sources, such as geothermal and hydroelectric. The architectural challenge lies in the relationship between the local communities and the big energy and industrial companies that need each other to thrive. Industrial structures and sites are usually quite universal in their own nature but architecturally the aforementioned relationship manifests in new industrial structures that are in a good dialogue with the local social and natural surroundings. This design research examines the potential of hydrogen production in Reykjanes, Iceland, for the purpose of utilizing clean energy technology specially to reduce flight and shipping emissions and then explores other uses, such as in land transport and exporting hydrogen to a global market. In addition, it will consider the social and spatial impact of a new eco- industrial park related to the hydrogen industry, in Helguvík, next to the town of Keflavík. By exploring the spatial qualities of the energy transition in Reykjanes, this design study provides valuable insight into the potential for utilizing hydrogen as a clean energy technology.